2003
DOI: 10.1152/japplphysiol.00419.2003
|View full text |Cite
|
Sign up to set email alerts
|

iNOS activity is essential for endothelial stress gene expression protecting against oxidative damage

Abstract: In endothelial cells, the expression of the inducible nitric oxide synthase (iNOS) and the resulting high-output nitric oxide synthesis have often been assumed as detrimental to endothelial function, but recent publications have demonstrated a protective role resulting from iNOS espression and activity. To address this question, we used antisense-mediated iNOS knockdown during proinflammatory cytokine challenge in primary endothelial cell cultures and studied endothelial function by monitoring the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 40 publications
1
35
0
1
Order By: Relevance
“…In addition, although endothelial damage was increased with aging as expected in the penile dorsal artery, L-NIL did not increase the apoptotic index, thus suggesting that agingrelated iNOS induction does not cause endothelial dysfunction. In fact, it has recently been claimed that iNOS may protect the endothelium in atherosclerosis [41]. This, together with the well known effects of NO in scavenging the profibrotic compound, ROS, thereby decreasing collagen synthesis and down-regulating its breakdown (see Refs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although endothelial damage was increased with aging as expected in the penile dorsal artery, L-NIL did not increase the apoptotic index, thus suggesting that agingrelated iNOS induction does not cause endothelial dysfunction. In fact, it has recently been claimed that iNOS may protect the endothelium in atherosclerosis [41]. This, together with the well known effects of NO in scavenging the profibrotic compound, ROS, thereby decreasing collagen synthesis and down-regulating its breakdown (see Refs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in both ECs and macrophages have shown that proinflammatory cytokine-induced HO-1 expression is at least partly dependent on iNOS expression and subsequent NO generation. 27,28 In a rat model of adjuvant arthritis, blockade of NO production from iNOS suppressed HO-1 upregulation at the site of inflammation. 29 These findings suggest that NO-mediated HO-1 expression may have important roles in preventing tissue damage associated with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Systemically, NO can lead to vasodilation and refractory hypotension. Finally, it is still highly debated what the role of iNOS is in atherogenesis with data to support both pro-and anti-atherogenic effects (21,31). These aspects of NO biology underly the importance of localizing iNOS gene transfer and fully evaluating the consequences of this treatment before clinical application.…”
Section: Discussionmentioning
confidence: 99%